The professional work of social workers at Cohab/Pará (1960-1980) - Miranda, Leonardo Costa; Santana, Joana Valente (Argumentum, 2024)
This article presents the results of a study that sought out and analysed the professional work of social workers in social work teams within the scope of urban and housing policies implemented by the Pará State Housing Company (Cohab/PA) between the 1960s and 1980s. It highlights the demands made of them, and their main responses. Based on the historical and dialectical materialism method, the study used bibliographical, documentary and field research, through interviews with social workers who worked at Cohab/PA during the period in question. It concludes that their work was polarised by conservative institutional demands and the demands of the working masses who were pressuring the government for answers to the housing issues.